MENDIDIK INTEGRITAS: KONSEP KESATUAN PRIBADI (EINHEIT DER PERSON) DI DALAM FILSAFAT PENDIDIKAN JULIAN NIDA-RÜMELIN - Reza A.A Wattimena (Studia Philosophica et Theologica, 2018)
This article describes the core meaning of integrity as the unity of person in the philosophy of Julian Nida-Rümelin. This concept is deeply embedded in the tradition of humanistic education. The method of this research is critical analysis on the book of Nida-Rümelin with title Philosophie einer humanen Bildung. Several critical remarks will also be given on the argument of this book. This article refers also the previous published books and articles by the article’s author. The education of human integrity means that the whole system and paradigm of education focus on the development of human being as a whole. The purpose is to create balanced and wholly integrated human being, which is an important point in the tradition of humanistic education. Tulisan ini menjabarkan inti pandangan Julian Nida-Rümelin tentang konsep kesatuan pribadi sebagai proses pendidikan integritas di dalam tradisi pendidikan humanis. Metode yang digunakan adalah analisis kritis terhadap tulisan Nida-Rümelin di dalam buku Philosophie einer humanen Bildung, sekaligus dengan mengacu pada penelitian yang telah dilakukan oleh penulis artikel ini sebelumnya. Beberapa tanggapan kritis juga akan diberikan terhadap pandangan Nida-Rümelin ini. Mendidik integritas berarti mendidik manusia dalam keseluruhan unsur dirinya. Ia menciptakan keseimbangan yang merupakan hal yang amat penting di dalam tradisi pendidikan humanis.